Analysis of The Impact of The Covid-19 Pandemic on The Performance of Indonesian Non Oil and Gas Exports - I Gusti Bagus Ngurah Diksa; Dewa Ayu Srijayanti (Politeknik Statistika STIS, 2021)
In 2020, Indonesia's exports decreased by 2.61 percent due to declining global and domestic demand during the COVID-19 pandemic. The decline in exports was not too deep due to the increase in non-oil exports by 16.73 percent, while non-oil exports fell by 10.10 percent. This shows the potential for non-oil exports to support the Indonesian economy during the pandemic. Seeing the impact of COVID-19 on export performance then used the ARIMA method. Based on the research, it was found that at the beginning of the COVID-19 pandemic, Indonesia experienced a slump in export performance, especially non-oil and gas. This is due to various policies regarding restrictions on mobility.